A multi‐institutional comparison of outcomes of immunosuppressed and immunocompetent patients treated with surgery and radiation therapy for cutaneous squamous cell carcinoma of the head and neck. Issue 11 (7th February 2017) - Manyam, Bindu V.; Garsa, Adam A.; Chin, Re‐I; Reddy, Chandana A.; Gastman, Brian; Thorstad, Wade; Yom, Sue S.; Nussenbaum, Brian; Wang, Steven J.; Vidimos, Allison T.; Koyfman, Shlomo A.
Abstract : BACKGROUND: Patients who are chronically immunosuppressed have higher rates of cutaneous squamous cell carcinoma of the head and neck (cSCC‐HN). This is the largest multi‐institutional study to date investigating the effect of immune status on disease outcomes in patients with cSCC‐HN who underwent surgery and received postoperative radiation therapy (RT). METHODS: Patients from 3 institutions who underwent surgery and also received postoperative RT for primary or recurrent, stage I through IV cSCC‐HN between 1995 and 2015 were included in this institutional review board‐approved study. Patients categorized as immunosuppressed had chronic hematologic malignancy, human immunodeficiency/acquired immunodeficiency syndrome, or had received immunosuppressive therapy for organ transplantation ≥6 months before diagnosis. Overall survival, locoregional recurrence‐free survival, and progression‐free survival were calculated using the Kaplan‐Meier method. Univariate and multivariate analyses were performed using Cox proportional‐hazards regression. RESULTS: Of 205 patients, 138 (67.3%) were immunocompetent, and 67 (32.7%) were immunosuppressed. Locoregional recurrence‐free survival (47.3% vs 86.1%; P < .0001) and progression‐free survival (38.7% vs 71.6%; P = .002) were significantly lower in immunosuppressed patients at 2 years. The 2‐year OS rate in immunosuppressed patients demonstrated a similar trend (60.9% vs 78.1%; P = .135) but did not meet significance. On multivariate analysis, immunosuppressed status (hazard ratio [HR], 3.79; P < .0001), recurrent disease (HR, 2.67; P = .001), poor differentiation (HR, 2.08; P = .006), and perineural invasion (HR, 2.05; P = .009) were significantly associated with locoregional recurrence. CONCLUSIONS: Immunosuppressed patients with cSCC‐HN had dramatically lower outcomes compared with immunocompetent patients, despite receiving bimodality therapy. Immune status is a strong prognostic factor that should be accounted for in prognostic systems, treatment algorithms, and clinical trial design. Cancer 2017;123:2054–2060 . © 2017 American Cancer Society . Abstract : Immunosuppressed patients with cutaneous squamous cell carcinoma of the head and neck have dramatically inferior outcomes compared with immunocompetent patients, despite bimodality therapy. Immune status is a strong prognostic factor that should be accounted for in prognostic systems, treatment algorithms, and clinical trial design.